Principle of Irremovability of Judges: Judicial Independence in Hungary - Aung, Nge Nge (Journal of Education Culture and Society, 2019)
Argument Principle of irremovability of judges is a norm of judicial independence not only in the EU framework but also in the international level.Judges of the Supreme Courts or the Constitutional Court are still removed even in the modern and developed countries. It is deeply related to the lack of independence of the judiciary in Europe and beyond Europe too. Results and Conclusion The results of the work can be applied in some countries that have not linked each other with regional integration policy ( like Myamar and ASEAN Countreies). The functions of the Constitutional Court are needed to be updated to protect the fundamental rights effectively in national level and the judiciary should be free from the influence of the legislature and the executive. Cognitive value To learn the best solution for the reconcilement among the three great branches of the government, especially to respect the independence of the judiciary and the principle of irremovability of judges widely accepted as not only international standards but also EU noem.